Analisis Kinerja Simpang Apill Empat Lengan (Studi Kasus: Simpang APILL Celep, Kota Sidoarjo) - Priyono, Arif; Hadi Putra, Kurnia; Sekartadji, Ratih; mca, Theresia (Jurnal Syntax Fusion, 2025)
The Celep APILL four-legged intersection is one of the signalized intersections located in Sidoarjo City. Traffic congestion frequently occurs at this location due to excessive vehicle volumes and inefficient signal timing. Therefore, this study aims to evaluate and analyze the performance of the intersection in addressing existing traffic problems. A review is necessary since this intersection experiences high traffic intensity, making it a critical congestion point during peak hours. The objective of this research is to determine the degree of saturation at the intersection under existing conditions and after the implementation of alternative solutions. Data analysis was conducted using field-observed traffic volume data, and the evaluation method referred to the Indonesian Road Capacity Manual (PKJI) 2023. Based on the calculations, the average degree of saturation under existing conditions exceeded 0.85, indicating noncompliance with PKJI 2023 standards and the need for corrective measures. The proposed solution involved modifying the signal phasing from the original three-phase configuration to a four-phase system. The results show that the degree of saturation for each approach became less than 0.85, indicating that the signal phasing modification meets the requirements of PKJI 2023